Analysis of the Effectiveness of Learning Models Among Rasa for Life and Inner Acting of Activating Material - Welly Suryandoko (Graduate School of Universitas Negeri Malang, 2023)
The purpose of this study is to test the effectiveness of the among rasa learning model for passion and inner acting of reactor material. This study uses data analysis in the form of percentage descriptive techniques and t-tests, namely (1) tests to determine the effectiveness of the among rasa learning model for passion and (2) tests to determine the effectiveness of the among rasa learning model for inner acting. The results of the study (1) the effectiveness of the learning model for the passion of calculating the significance value. A sig (2-tailed) of 0.000 or a significance of less than 0.05 (0.000 less than 0.05). (2) the effectiveness of the learning model for inner Acting obtained a Sig significance value (2- tailed) of 0.000 or a significance of less than 0.05 (0.000 less than 0.05)